2017
DOI: 10.1002/cne.24205
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐tuning light sensitivity in the starry flounder (Platichthys stellatus) retina: Regional variation in photoreceptor cell morphology and opsin gene expression

Abstract: Vertebrate color vision relies on the differential expression of visual pigment proteins (opsins) in cone photoreceptors of the retina. The diversity of opsins and their retinal expression patterns appear greatest for animals that experience variable light habitats, as is the case with flatfishes. Yet, opsin repertoires and expression patterns in this group of fishes are poorly described. Here, we unveil the visual opsin expression patterns of juvenile starry flounder (Platichthys stellatus) and describe the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 60 publications
(103 reference statements)
1
31
0
Order By: Relevance
“…These bandwidths were also greater than those predicted for such pigments using empirical models based on opsin conjugation to A1 retinal chromophore 3 (Table 1 ). Such results suggested the contribution of multiple opsins to the S (445) and M (536) visual pigment absorbance curves since analyses of retinal extracts using High Performance Liquid Chromatography revealed the same A1 retinal chromophore as present in younger fish 34 (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…These bandwidths were also greater than those predicted for such pigments using empirical models based on opsin conjugation to A1 retinal chromophore 3 (Table 1 ). Such results suggested the contribution of multiple opsins to the S (445) and M (536) visual pigment absorbance curves since analyses of retinal extracts using High Performance Liquid Chromatography revealed the same A1 retinal chromophore as present in younger fish 34 (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 77%
“…In a previous investigation, eight visual pigments were measured, using microspectrophotometry, that corresponded to seven cone opsins and one rod opsin (whose transcripts were quantified by digital PCR) in the retina of the young, post-metamorphic starry flounder (~5–15 g in weight) 34 . The correspondence between visual pigments and opsin types was as follows: UV(369)-SWS1, S(415)-SWS2B, S(437)-SWS2A2, S(456)-SWS2A1, M(527)-RH2A1, M(545)-RH2A2, L(557)-LWS, and rod (507)-RH1.…”
Section: Introductionmentioning
confidence: 99%
“…Microspectrophotometry data indicate that all are translated and that just one type of chromophore is used (9). We predicted opsin expression would be modified by a seven-week exposure to distinct light environments and that changes in opsin expression over that length of time would influence vision.…”
Section: Opsin Expression Plasticity In Response To Light Environmentmentioning
confidence: 99%
“…It may be that a large visual opsin repertoire is a 'toolkit', with subsets of opsins used at different stages of development, in different light environments, or indeed in particular regions of the retina. Several authors have reported observations consistent with this hypothesis: developmental variation (6), geographic distribution based on light environment (7), and regions of the retina (8,9). Despite correlations between opsin repertoire or expression patterns and the light environment, clear connections between variation in opsin expression and visual performance have rarely been demonstrated outside of humans.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation